El lugar del enemigo (2013)
ABSTRACT: The research on which this text is based established that the logics of the construction of the enemy in the discourse of the armed groups involved in the Colombian conflict are manifested in four perspectives: absolute enemy, political enemy, necessary enemy, and accidental enemy. Based on the tenets of psychoanalysis, this article enquires about the relationship between these four dimensions of the enemy and the modalities of social links, on the one hand; and on the other, the subjective foundation that makes it possible that enmity arises at any stage of our civilization, since it is here where this issue has weight and it has a value of reality.